Real-Time Glyphosate Detection Using a Colorimetric Optical Sensor - Ahmad, Khairul Azman; Abdullah, Noramalina (International Journal of Integrated Engineering, 2025)
The availability of clean water is a growing global concern, exacerbated by pollutants such as glyphosate, a common herbicide. Conventional detection methods are often time-consuming and require laboratory analysis, which risks sample degradation. This study introduces the development of an in-situ colorimetric optical sensor for glyphosate detection, providing an integrated, real-time solution. The sensor utilizes a reaction between glyphosate and 2,4-dinitrofluorobenzene (DNFB), producing a yellow-colored compound as an indicator. A regression model was developed to estimate glyphosate concentration, and the sensor’s performance was compared with a spectrophotometer, yielding coefficients of determination of 0.9079 and 0.9715, respectively. While the spectrophotometer showed higher accuracy, the colorimetric sensor offers a cost-effective, portable, and reliable method for on-site monitoring, aligning with integrated engineering approaches for environmental management.